Islamic Tolerance on Religious Freedom, Culture and Thought in Andalusia - Meirison Meirison (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2020)
Andalusian civilization was formed by a combination of complex societies consisting of Arabs, Berbers, Goths, Israelis, Africans, and Salsabes. Logically it is difficult for multi-ethnic communities to coexist peacefully. This social mosaic is a challenge when Islam entered Andalusia. That is because Islam was born in the Arabian Peninsula which has a different culture from Andalusia. Based on the problem of how the influence of Islamic and Muslim tolerance on freedom of religion, culture and thought in Andalusia and through literature study with a historical approach; data collection (heuristic), verification, interpretation and historiography, the authors get the conclusion that cultural assimilation has interacted with tolerance as an influence of Islamic teachings. The influence is not only limited to the development of teachings, but the life of the Andalusian people. For example the birth of the Moor and Mozarabic groups, the development of linguistics and politics. Another indication is the attitude of the Andalusian community and especially Muslims who tolerate religious schools, sects that are different from Islam. Andalusian people lived side by side peacefully for centuries. Educated Jewish and Christian communities are satisfied with their situation under Islamic hegemony and its laws.